Industry technology survey a survey of the architectural, engineering and construction (AEC) design and documentation technologies in the petroleum retail industry - Ramirez, Mario J. (Quezon City University of the Philippines Diliman, 2006)
The Marketing group has a huge responsibility in the petroleum retail business (hereon referred to in this report as "oil" business, company and industry). As the group responsible for the competitiveness of the company's retail marketing and sales, it must ensure that its design capabilities are efficient, flexible, produce quality output and up to date. The oil companies started acquiring and deploying Computer Aided Design (CAD) technology back in the latter half of the 1980's, when the technology was still in its infancy in the country. It gradually replaced manual methods of design and drafting. In the early 1990's, some of the companies also experimented with 3D visualization technologies as part of the design process. These investments in design technologies reflect the competitiveness in the oil industry where every fraction in market share is vigorously contested, and are also reactions to the technology imperative, where they have to acquire technology to keep up with competitors. The acquisition and utilization of AEC (Architectural, Engineering & Construction) systems in the industry has evolved, in fits and starts, since the first CAD systems were installed. The ideal has always been to enhance operations and competitiveness with current technology. However, there are factors that inhibit this aim from realization, such as the cost of the technology, skill requirements and established systems or standards. But as capital and operational decisions become more and more cost-significant, it is important that design decisions be arrived at in the most efficient manner possible in order to avoid costly mistakes, enhance quality and encourage innovation. This technology survey is done in support of these efforts. The study surveys the use of AEC design and documentation technologies in the local oil industry. The gasoline station design groups of seven oil companies were included in the study (an eighth declined). The results indicated general acceptance of design and documentation technologies such as Computer Aided Design (CAD) software. However, there appears to be a need to improve the outlook of the design group as well as management with regard to advanced technology and what effects and impacts of its developments have on the industry, and in retail design in particular. This study was influenced by studies of much larger industries such as the manufacturing and construction industries. After having completed this survey, it is the researcher's opinion that this type of study will also be very useful for the equivalent local industries.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Petroleum industry and trade; Industry technology survey